2020
DOI: 10.1016/j.psj.2019.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Growth, carcass characteristics, and meat quality of broilers fed a low-energy diet supplemented with a multienzyme preparation

Abstract: The effect of a low-ME diet with a multienzyme (Kemzyme Plus, Kemin, Des Moines, IA) blend on performance, meat quality, and carcass traits was evaluated in Hubbard broiler chicks. A total of 120 Hubbard broiler chicks were allocated to the following 4 experimental groups and every group was separated into 6 replicates, with 5 birds per replicate: control (3,180 kcal/kg of ME), control + 0.50 g/kg diet of enzyme (Cont-Enz), low-ME diet (3,080 kcal/kg), and low-ME + 0.50 g/kg diet of enzyme (low-ME-Enz). The tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
25
2
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 37 publications
14
25
2
2
Order By: Relevance
“…The results of the carcass organs were in agreement with the other researchers' results (Liu et al, 2007;Hussein et al, 2019Hussein et al, , 2020. Farran et al (2010) reported that the muscle weights were not affected by the inclusion of enzyme preparations.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results of the carcass organs were in agreement with the other researchers' results (Liu et al, 2007;Hussein et al, 2019Hussein et al, , 2020. Farran et al (2010) reported that the muscle weights were not affected by the inclusion of enzyme preparations.…”
Section: Discussionsupporting
confidence: 91%
“…However, the combination of xylanase, amylase, and protease works better than protease supply alone (Olukosi, 2007). This method could reduce the number of raw matter ingredients needed for poultry diets such as yellow maize and soy meal, and reduce production costs (Hussein et al, 2019(Hussein et al, , 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Conflicting with our findings, Cho et al [ 45 ] concluded that emulsifier and multienzyme in low-density diets could increase the relative bursa weight. A recent study reported that a low-energy-density diet could increase chicken bursa weight [ 46 ]. High-energy diet could also be associated with the roles of the bursa in poultry birds.…”
Section: Discussionmentioning
confidence: 99%
“…Feed additives are generally considered materials used to enhance the effectiveness of nutrients and exert their effects on improving poultry performance (Ashour et al., 2020; Farag & Alagawany, 2019; Saeed, Alagawany, et al., 2019). There are a number of feed additives used in poultry feed, such as antibiotics, probiotics, oligosaccharides, enzymes and organic acids (Bin‐Jumah et al., 2020; Elgeddawy et al., 2020; Hussein et al., 2020; Windisch et al., 2008). They are included in the diet of poultry and animals for promoting growth through their potential effect in increasing feed intake (FI; Demir et al, 2003; Mahrose et al., 2019; Wang et al., 2019; Yatoo et al., 2017).…”
Section: Introductionmentioning
confidence: 99%